RANCANG BANGUN MICROBUBBLE GENERATOR (MBG) UNTUK MENINGKATKAN OKSIGEN TERLARUT (DO) PADA BUDIDAYA PERIKANAN - Pratiwi, Citra Zaskia; Mawardi, Iman; Nugroho, Faizin Adi (Chanos Chanos, 2022)
Microbubble generator (MBG) is one of aerator that used to enhance dissolved oxygen (DO). Microbubble generator is designed with the diameter of 45 mm for water inlet and reduced to the diameter of 10 mm. The air inlet has the diameter of 18 mm and increased to 45 mm so that it can be equal with the nozzle diameter. The nozzle is the outlet of water and air is reduced to the diameter of 22 mm. The test results showed that the minimum DO measured of 6.3 mg/l, and the maximum of 6.9 mg/l. The increase in DO ranged from 2.3 – 2.7 mg/l. The measured electric motor temperature ranged from 45°C - 55°C for 9 days of testing so that it can be stated that the microbubble generator can be used for 1 cycle of aquaculture.